PENGARUH STRATEGI PEMASARAN TERHADAP PENINGKATAN VOLUME PENJUALAN LAHAN DI PT. KAWASAN INDUSTRI MODERN (PERSERO) MEDAN - Charles Sianturi; Julia Mintasari Simanjuntak (LPPM Universitas HKBP Nommensen, 2021)
This study aims to determine the effect of marketing strategies, namely pricing strategies and promotional costs carried out by PT. Kawasan Industri Modern (Persero) to increase the volume of land sales. The method used is a quantitative method. This study uses secondary data types and the data analysis used is multiple regression data analysis, partial regression analysis and equipped with classical assumption test. The results of the regression analysis show that partially the pricing strategy has a positive and significant effect on increasing the volume of land sales. Simultaneous or multiple regression testing of pricing and promotion strategies obtained constant values ​​and positive regression coefficients. And the value of R Square shows 0.75.3 or 75.3% which means that the marketing strategy carried out by PT. Kawasan Industri Modern (Persero) can be explained by the variable pricing strategy and promotion strategy while the remaining 24.7% is influenced by other factors not examined in this study. From the results of this study, it can be concluded that partially price and promotion have a positive and significant effect on increasing the volume of land sales and simultaneously price and promotion have a positive and significant effect on increasing land sales volume. Thus it can be suggested that PT. Kawasan Industri Modern (Persero) continues to carry out pricing strategies and also promotional costs that have a good impact on increasing land sales at PT. Kawasan Industri Modern (Persero).